An investigation into treatment options to improve the performance of re-used seed crystals for gypsum precipitation in the presence of an anti-scalant - Cronje, Izak Adolf (Stellenbosch : Stellenbosch University., 2020)
Thesis (MEng)--Stellenbosch University, 2020.